2012
DOI: 10.1063/1.3690071
|View full text |Cite
|
Sign up to set email alerts
|

Stokes number effects on particle slip velocity in wall-bounded turbulence and implications for dispersion models

Abstract: The particle slip velocity is adopted as an indicator of the behavior of heavy particles in turbulent channel flow. The statistical moments of the slip velocity are evaluated considering particles with Stokes number, defined as the ratio between the particle response time and the viscous time scale of the flow, in the range 1 < St < 100. The slip velocity fluctuations exhibit a monotonic increase with increasing particle inertia, whereas the fluid-particle velocity covariance is gradually reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
35
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 18 publications
(30 reference statements)
11
35
2
Order By: Relevance
“…In the core region of the channel, the fibre orientation was found to be isotropic. Mortensen et al 15,16 and Zhao et al 17,18 also observed that the particle slip velocity ) ( v u u   is largely dependent on the particle's distance from the wall (a measure of the fluid velocity gradient), and that lighter particles show a positive slip velocity whilst heavier particles exhibit a negative slip velocity in the viscous sub-layer but a positive value in the buffer layer.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the core region of the channel, the fibre orientation was found to be isotropic. Mortensen et al 15,16 and Zhao et al 17,18 also observed that the particle slip velocity ) ( v u u   is largely dependent on the particle's distance from the wall (a measure of the fluid velocity gradient), and that lighter particles show a positive slip velocity whilst heavier particles exhibit a negative slip velocity in the viscous sub-layer but a positive value in the buffer layer.…”
Section: Introductionmentioning
confidence: 97%
“…as it is at a distance from the wall at which the magnitudes of the mean slip velocity and the slip velocity fluctuations reach a maximum for spherical particles 17,18 . The next plane considered is also in the buffer Table 1 8, [14][15][16]18 .…”
Section: Instantaneous Fibre Concentrationmentioning
confidence: 99%
“…In this work its effect was neglected for the sake of improving understanding of fluid-particle interaction within a manageable parameter range. This is common practice in the DNS and LES of particleladen, two-phase flow in a channel (Wang and Squires, 1996b;Wang and Squires, 1996a;Marchioli et al, 2008;Mortensen et al, 2008a, b;Marchioli et al, 2010;Zhao et al, 2012). For small sizes of ellipsoidal particles, the drag force also exhibits a greater influence on the particle dynamics than the lift force (Wang et al, 1997;Pan et al, 2001).…”
Section: Translational Motionmentioning
confidence: 99%
“…Some of the statistical results which will be presented in § 6 of this paper were obtained by conditional sampling rather than by conventional Reynolds-averaging. Conditional sampling has been used before in one-way coupled simulations, for instance by Squires & Eaton (1990), Mortensen et al (2007Mortensen et al ( , 2008 and Zhao, Marchioli & Andersson (2012). The fluid velocity of interest is that at the particle positions, since only that velocity is involved in the Stokes drag force in (2.5).…”
Section: Computer Simulationsmentioning
confidence: 99%